Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
5^(x+1) - 5^x = 100.25^99
=> 5^x.5 - 5^x = 4.25.25^99
=> 5^x .4 = 4. 25^100
=> 5^x = (5^2)^100
=> 5^x= 5^200
=> x=200
Vậy x=200
Mình chỉ làm cho bạn câu d và e thôi
d) ( 1 - 1/2 + 1/2 - 1/3 + 1/3 - 1/4 +....... +1/99 - 1/100 ) . (x - 3)=1
( 1 - 1/100 ) . (x - 3 )=1
99/100.(x -3)=1
x - 3 = 1:99/100
x - 3 =100/99
x = 100/99 + 3
x = 397/99
e) (1/2 . (1 - 1/3 + 1/3 - 1/5 + 1/5 -1/7 +.....+1/99 - 1/101 ) . (x+2) =3/101
(1/2 . ( 1 - 1/101 ).(x+2)=3/101
(1/2 . 100/101 ) . (x + 2) =3/101
100/202 . ( x + 2 )= 3/101
50/101 . (x + 2 ) = 3/101
x + 2 = 3/101 :50/101
x+2=3/50
x =3/50-2
x= -97/100
Ta có : \(\frac{x-1}{5}=\frac{y-2}{2}=\frac{z-2}{3}=\frac{2y-4}{4}=\frac{x-1+2y-4-\left(z-2\right)}{5+4-3}=\frac{x-1+2y-4-z+2}{6}\)
\(=\frac{x+2y-z-3}{6}=\frac{3}{6}=\frac{1}{2}\)
Nên : \(\frac{x-1}{5}=\frac{1}{2}\Rightarrow x-1=\frac{5}{2}\Rightarrow x=\frac{7}{2}\)
\(\frac{y-2}{2}=\frac{1}{2}\Rightarrow y-2=1\Rightarrow y=3\)
\(\frac{z-2}{3}=\frac{1}{2}\Rightarrow z-2=\frac{3}{2}\Rightarrow z=\frac{7}{2}\)
Vậy ,,,,,,,,,,,,,,,,,,
a) \(\frac{x-3}{x+5}=\frac{5}{7}\)
\(\Rightarrow\left(x-3\right).7=\left(x+5\right).5\)
\(\Rightarrow7x-21=5x+25\)
\(\Rightarrow7x-5x=21+25\)
\(\Rightarrow2x=46\)
\(\Rightarrow x=23\)
Vậy \(x=23\)
b) \(\frac{7}{x-1}=\frac{x+1}{9}\)
\(\Rightarrow\left(x-1\right).\left(x+1\right)=7.9\)
\(\Rightarrow\left(x-1\right)x-\left(x+1\right)=7.9\)
\(\Rightarrow x^2-x-x-1=63\)
\(\Rightarrow x^2-1=63\)
\(\Rightarrow x^2=64\)
\(\Rightarrow x=8\) hoặc \(x=-8\)
Vậy \(x=8\) hoặc \(x=-8\)
c) \(\frac{x+4}{20}=\frac{5}{x+4}\)
\(\Rightarrow\left(x+4\right)^2=100\)
\(\Rightarrow x+4=\pm10\)
+) \(x+4=10\Rightarrow x=6\)
+) \(x+4=-10\Rightarrow x=-16\)
Vậy \(x\in\left\{6;-16\right\}\)